(untitled) (Research, Society and Development, 2020)
New technologies are under study with a view to the use of agro industrial wastes in the development of bioprocesses, for example for the production of biofuels, energy, plastics and inputs in the food and beverage industries. The aim of this study was to realize the state of the art on the use of agro-industrial residues for the production of cellulase. The methodology adopted was exploratory and descriptive research, using scientific publications from the last decade. It was found that a market of importance for bioprocesses are commercial enzymes produced by microorganisms that use agro-industrial residues as nutrients, which have proved to be a viable option when compared to their chemical counterparts. Cellulase is the third most used enzyme in several processes, behind proteases and amylases, whose demand is increasing in industrial applications, such as in detergents, textiles, paper processing, animal feed, fruit juice, food, drinks and biofuels. Cellulases are inducible enzymes synthesized by a wide variety of microorganisms. The composition of the microorganism growth medium can significantly affect the cellulase yield and productivity and is important in the development of industrial bioprocesses. The use of agro-industrial waste is an interesting strategy for reducing the costs associated with the culture medium composition, as an economical and ecologically viable alternative for the destination of these resources and the production of enzymes on a large scale.